Farmer-led Adaptation: Best Practice Case Studies - Chevallier, Romy; Gosling, Amanda; Cramer, Laura K. (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
Produced by the Eastern Africa Farmers Federation (EAFF) and the Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA), this report presents ten case studies that highlight existing farmer-led climate adaptation initiatives across Africa. The report seeks to showcase innovative, farmer-driven solutions and to demonstrate their significant impact on climate adaptation and resilience building. Through the documentation of these approaches, the initiative aims to promote the wider adoption of effective practices, inform policy, and attract financial support to scale locally led adaptation strategies.